Evaluasi Proses Pencatatan Persediaan Dalam Meningkatkan Transparansi Keuangan Pengalaman Magang di Hotel Lombok Plaza - Apriani, Lestari Ayu; Baiq Nadia Nirwana (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
This community service activity was carried out through a fieldwork program at Lombok Plaza Hotel, specifically in the storekeeper division. The aim of this activity is to highlight the crucial role of inventory management in ensuring financial transparency and operational efficiency within the hospitality industry. Proper inventory recording supports accurate financial reports, reduces the risk of stock discrepancies, and strengthens decision-making in daily operations. The method applied during the internship was direct observation and hands-on practice, including recording the inflow and outflow of goods, updating stock data in the RAPP-Shortcut system, checking item availability, and managing procurement from suppliers. The results of this program indicated that systematic inventory management helps minimize errors, improves stock control, and supports transparency in financial reporting. Furthermore, students gained valuable experience in applying theoretical knowledge of management and accounting in a real work environment, while developing technical, analytical, and communication skills. In conclusion, this activity emphasized the importance of accurate inventory recording as a foundation for financial transparency and sustainable hotel operations, while also providing practical learning outcomes for students in preparing for professional careers.